Uncertainties and Risk Assessment in Trade Relations - Ojo, Marianne (USA : IGI Global, 2018)
"This book considers strategic and economic relations - as well as alliances and the significance of the incoming US administration for global relations - in matters not just related to trade and security, but also financial stability.
Includes index.
Keywords: International economic relations